2013
DOI: 10.1007/s12665-013-2588-4
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical and isotopic evolution of groundwater in the Wadi Watir watershed, Sinai Peninsula, Egypt

Abstract: The Wadi Watir delta in the Wadi Watir watershed is a tourist area in the arid southeastern part of the Sinai Peninsula, Egypt, where development and growth of the community on the delta are constrained by the amount of groundwater that can be withdrawn sustainably. To effectively manage groundwater resources in the Wadi Watir delta, the origin of groundwater recharge, groundwater age, and changes in groundwater chemistry in the watershed needs to be understood. Mineral identification, rock chemistry, water ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…2b), and this highly saline groundwater mainly originated from three sequential sea transgressions and regressions during the Pleistocene epoch (Abbas et al, 2004;Mabrouk and Nasr, 1997). The fresh groundwater in the Wadi Watir delta aquifers has been affected by mixing with this older deep saline groundwater that is approximately 2400e3600 years old (Eissa et al, 2013a). The Cl concentration and Cl/Br ratio data confirm that groundwater salinization in the Wadi Watir delta aquifers primarily originates from upwelling of a deep saline groundwater, which is caused by overpumping.…”
Section: Groundwater Geochemistrymentioning
confidence: 72%
See 2 more Smart Citations
“…2b), and this highly saline groundwater mainly originated from three sequential sea transgressions and regressions during the Pleistocene epoch (Abbas et al, 2004;Mabrouk and Nasr, 1997). The fresh groundwater in the Wadi Watir delta aquifers has been affected by mixing with this older deep saline groundwater that is approximately 2400e3600 years old (Eissa et al, 2013a). The Cl concentration and Cl/Br ratio data confirm that groundwater salinization in the Wadi Watir delta aquifers primarily originates from upwelling of a deep saline groundwater, which is caused by overpumping.…”
Section: Groundwater Geochemistrymentioning
confidence: 72%
“…Model results were compared to and calibrated using observed seawater intrusion along the coast (identified using water chemistry and isotopic data), salinity increases in the main well field water, estimated groundwater recharge from an earlier study (Eissa et al, 2013a), and observed pumping data.…”
Section: Solute-transport and Flow Dynamics Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the origin and quality of groundwater is important for sustainable development and effective management of groundwater resources in arid regions (Eissa et al 2014) However, it is difficult to determine the amounts and sources of groundwater recharge using conventional water balance and/or hydraulics methods. Combined hydrogeochemical and isotopic studies may help elucidate both the sources of groundwater recharge and groundwater hydrogeochemical evolution processes (Bouchaou et al 2008;Gárfias et al 2010;Parisi et al 2011;Diaw et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Common methods in this respect include the chloride mass balance method, use of hydrogeochemical tracers (minor or trace metals), and determination of isotopic composition. These techniques can be used to identify sources of groundwater and estimate the contribution of each member (Vanderzalm et al 2011;Al-Charideh and Hasan 2013;Schulz et al 2013;Eissa et al 2014). In arid regions, where there is little precipitation but strong evaporation, hydrogeochemical indicators and stable isotopic groundwater compositions can be effectively employed to trace recharge sources and quantify relative evaporation (Nativ et al 1997;Vanderzalm et al 2011;Yangui et al 2011;Singh et al 2012;Ahmed et al 2013;Lapworth et al 2013).…”
Section: Introductionmentioning
confidence: 99%